Scaling Up Coral Reef Restoration Using Remote Sensing Technology - Foo, Shawna A.; Asner, Gregory P. (Frontiers in Marine Science, 2019)
Coral reefs face an uncertain future and may not recover naturally from anthropogenic climate change. Coral restoration is needed to rehabilitate degraded reefs and sustain biodiversity. There is a need for baseline data on global reef distribution, composition and condition to provide targets for conservation and restoration. Remote sensing can address this issue and is currently underutilized in reef research and restoration. This synthesis integrates current capabilities of remote sensing with key reef restoration criteria to facilitate coral restoration success. Development of a spectral database for corals, linking habitat type and extent with predator abundance, and identification of species-specific acoustic signatures are needed to drive forward the use of remote sensing in reef restoration design and monitoring. Reciprocally, reef restoration efforts should innovate at ecosystem, regional and global levels using remote sensing, to preserve as much of the coral reef biome as possible with continued ocean-climate change.